Validation of the Multiple Sensor Mechanism of the Keap1-Nrf2 System - Takaya, Kai (2012)
The Keap1-Nrf2 system plays a critical role in cellular defense against electrophiles and reactive oxygen species. Keap1 possesses a number of cysteine residues, some of which are highly reactive and serves as sensors for these insults. Indeed, point mutation of Cys151 abrogates the response to certain electrophiles. However, this mutation does not affect the other set of electrophiles, suggesting that multiple sensor systems reside within the cysteine residues of Keap1. Precise contribution of each reactive cysteine to the sensor function of Keap1 remains to be clarified. To elucidate the contribution of Cys151 in vivo, in this study we adopted transgenic complementation rescue assays. Embryonic fibroblasts and primary peritoneal macrophages were prepared from mice expressing the Keap1-C151S mutant. These cells were challenged with various Nrf2 inducers. We found that some of the inducers triggered only marginal responses in Keap1-C151S-expressing cells, while others evoked responses in a comparable magnitude to those observed in the wild-type cells. We found that tert-butyl hydroquinone, diethylmaleate, sulforaphane and dimethylfumarate were Cys151-preferable, whereas 15-deoxy-Δ(12,14)-prostaglandin J(2) (15d-PG-J(2)), 2-cyano-3,12 dioxooleana-1,9 diene-28-imidazolide (CDDO-Im), ebselen, nitro-oleic acid and cadmium chloride were Cys151-independent. Experiments with embryonic fibroblasts and primary macrophages yielded consistent results. Experiments testing protective effects against the cytotoxicity of 1-chloro-2,4-dinitrobenzene of sulforaphane and 15d-PG-J(2) in Keap1-C151S-expressing macrophages revealed that the former inducer was effective, while the latter was not. These results thus indicate that there exists distinct utilization of Keap1 cysteine residues by different chemicals that trigger the response of the Keap1-Nrf2 system, and further substantiate the notion that there are multiple sensing mechanisms within Keap1 cysteine residues.